FAKTOR-FAKTOR YANG MEMENGARUHI KEGAGALAN JASA DI RUMAH SAKIT RAFLESIA BENGKULU DAN DAMPAKNYA PADA PERILAKU KOMPLAIN PASIEN - Fachri Eka Saputra; Muhammad Najib Murti (UNIB Press, 2020)
The purpose of this research is to test factors that causing service failure at the Raflesia Hospital and to determine the influence of service failure factors on the patient’s complaint behavior. Quantitative research design is used in this study. Data collection method conducted by hand-delivery survey with using questionnaire. The respondents of this study are the patient’s or their families who came to the raflesia hospital to get treatment for healty condition. Accidental sampling technique was used in this study because all of people who came to the hospital were usually familiar with the service in the hospital and their deserved to be the respondent. Data collected were analysed by using two combination of statistical method, namely: analysis factor and multiple regression analysis. This study found that: 1) there are six factors causing service failure in the raflesia hotel at Bengkulu city, namely: lack of empathy, expensive rates, room discomfort, Reliability, insufficient facilities, and lack of responsiveness; 2) all of these factors have positive and significant influence to the patient’s complaint behavior. Manager at the raflesia hospital have to pay attention to these factors to improve patient’s comfort and complacency to overcome service failure in the future. Practical and empirical contribution are also elaborated in this study.